ISTITSNA’ IN SURAH AL-AN’AM: MEANINGS AND ITS IMPLICATION - Muzdalifah, Zahrotul (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2019)
This research aimed to describe the type and functions of istitsna? in Surah al-An?am, the meanings of ?adawat istitsna? and the implication for Arabic teaching and learning. The research design is descriptive qualitative. The result of this research, istisna? phrases in Surah al-An?am based on type and function, those are istitsna? muttashil which function is li takhsis, istitsna? munqathi' which function is li istidrak and istisna? 'mufarragh which function is li hasr. The ?adawat isttisna' is not always meaningless "except" (kecuali/selain) but it can also mean "only"/"nothing but? (hanya/tidak lain hanyalah) in certain patterns. The implication of this research, there are 14 selections of patterns of istitsna? that can be implemented in Arabic teaching and learning. For example, the patterns represented in understanding the theories of istitsna? and the production of sentences by istitsna? patterns for both of speaking or writing